Influence Of Administrator Of Institutions On Students’ Academic Achievement In General Mathematics Between Mission – Government Partnered And Sole Government Administered Secondary Schools: Nigeria Perspective - Tochukwu Christian Nwokwu (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
The purpose of this research is to ascertain the mean achievement score of the students in mathematics who wrote Senior Secondary Certificate Examination (SSCE) in mission – government partnered and sole government administered secondary schools; to determine the influence of administrator of institution. The population of the study is 2,982, which are the total students who wrote Senior Secondary Certificate Examination (SSCE) mathematics for the period between 2018 and 2020 for both mission – government partnered and sole government administered secondary schools in the study area. The sample size is 298. Three (3) research questions were prepared. Null and alternate hypothesis were developed. The data collected was obtained by the researcher from the exam body - The Post Primary Schools Management Board (PPSMB) Enugu, as well as, the different senior secondary schools involved in this research that are located in Enugu South Local Government Area of Enugu State, Agbani Zone. The data was analyzed using descriptive statistics (mean, for research questions) and T-test for the hypothesis. For Distinction and Credit HA is accepted and for Pass HA is rejected. In conclusion, in order to function in a mathematically literate way in the future, students must have a strong foundation in mathematics in their elementary school years. It is highly recommended that Mathematics should be taught by teachers who have a strong knowledge of mathematical content and pedagogy.